Growth, instability and cycles: Harrodian and Kaleckian models of accumulation and income distribution - Peter Skott (University of Massachusetts, Department of Economics, 2008)
This paper compares Kaleckian and Harrodian models of accumulation. The simplicity of the canonical Kaleckian model is appealing but more complex Harrodian specifications are preferable from a behavioral perspective. The local instability of Harrodian-inspired specifications, moreover, offers a unified understanding of both trend and cycles.
Keywords: E12; E32; O41; 330; Kalecki; Harrod; Kaldor; Robinson; Steindl; investment function; stability; growth cycle; reserve army; multiple equilibria; Wachstumstheorie